The Effects of Corporate Innovation, Directors with Overseas Experience, and Institutional Ownership on Tax Avoidance (A Study of Manufacturing Companies Listed on the Indonesia Stock Exchange from 2019 to 2023) - Natasya Destiani (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2025)
Differences in perspectives on taxation between the government and taxpayers encourage companies to minimize their tax payments through tax avoidance strategies. Such practices have the potential to reduce government tax revenues and create long-term fiscal risks. This study aims to examine the effects of corporate innovation, directors with international experience, and institutional ownership on tax avoidance among manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. This study adopts a quantitative approach using secondary data obtained from companies' annual reports. The sample was selected through purposive sampling, resulting in 39 manufacturing companies with a total of 195 firm-year observations over five years. Data were analyzed using multiple linear regression following the classical assumption tests. The findings indicate that corporate innovation has a positive effect on tax avoidance, suggesting that innovative firms are more likely to adopt efficient strategies for managing their tax burden. In contrast, institutional ownership has a negative effect on tax avoidance, indicating that monitoring by institutional investors can discourage tax avoidance practices. Meanwhile, directors with international experience do not have a significant effect on tax avoidance. This study provides practical implications for policymakers and corporate stakeholders in developing governance policies that promote tax compliance. From an academic perspective, the findings contribute to the literature by enriching the understanding of non-financial determinants influencing corporate tax avoidance strategies.